A Prospective Randomized Controlled Trial: Alternative Approach to EEG Application to Reduce Electrode-induced Skin Injury among Ambulatory EEG Patients. (2nd January 2022) - Ouchida, Sumika; Nikpour, Armin; Fairbrother, Greg
ABSTRACT: Ambulatory electroencephalography (AEEG) is a technique of continuous EEG recording of patients in their natural setting, outside the controlled environment of the hospital. Electrode-induced skin injury is a common complication of prolonged EEG monitoring. This randomized study aimed to investigate the performance of two methods of electrode application in reducing electrode-induced skin injury among patients undergoing 4-day AEEG monitoring. A randomized interventional study was conducted from November 2020 to May 2021 in the Neurosciences Ambulatory Care Unit at a metropolitan hospital in Sydney, Australia. We enrolled patients into two groups: i) Group 1 (standard protocol group) received Ten20 Conductive Paste TM with Tensive® adhesive gel as the primary approach to electrode application and ii) Group 2 (intervention group) received Ten20 Conductive Paste TM with Tensive® adhesive gel and hydrogel electrodes on hairless locations as the primary approach to electrode application. A total of 79 patients participated in this study. The group that received the addition of hydrogel electrodes (Group 2) performed better than the standard protocol group on electrode site inflammation for the frontal region, particularly FP1, FP2, F8, and the ground electrode sites. EEG quality and self-reports of patient comfort and mood did not differ significantly between the two groups. The addition of hydrogel electrodes using a Ten20 Conductive Paste TM with a Tensive® adhesive gel protocol results in reduced inflammation at frontal lobe and ground electrode sites.